2009
DOI: 10.1186/gb-2009-10-11-r132
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry-related assortative mating in Latino populations

Abstract: Examination of ancestry-informative genetic markers shows that Puerto Rican and Mexican populations have shown strong assortative mating that continues to this day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
119
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 32 publications
10
119
2
Order By: Relevance
“…assortative mating | genomic ancestry | homogamy M ate selection in human populations is a topic of broad general and academic interest, with important implications for economics (1), sociology (2), psychology (3), and genetics (4,5). Studies from all of these fields have uncovered myriad genetic and socioeconomic factors that are correlated between partners.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…assortative mating | genomic ancestry | homogamy M ate selection in human populations is a topic of broad general and academic interest, with important implications for economics (1), sociology (2), psychology (3), and genetics (4,5). Studies from all of these fields have uncovered myriad genetic and socioeconomic factors that are correlated between partners.…”
mentioning
confidence: 99%
“…Recent work from several groups suggests that genetic factors contribute to human mating preferences (5,(7)(8)(9)(10). In European populations, there is evidence that individuals tend to be attracted to people with major histocompatibility complex (MHC) regions that are distinct from their own (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This panel of markers has been used to characterize admixture proportions in previous studies (Pereira et al, 2012; Risch et al, 2009). Briefly, Yaeger's panel includes biallelic single nucleotide polymorphisms (SNPs) that were selected from the Affymetrix Human 100K SNP chip, based on their information content to infer Native American, European, and African ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…also showed that this increase is directly proportional to the variance of the genotype frequency between sub-populations when the same genotypes comprise the mating types. Sub-population or ancestry-related positive assortative mating (Risch et al, 2009; results in population stratification, and is seen at all loci where the allele frequency differs between sub-populations.…”
Section: Introductionmentioning
confidence: 99%